Diagnostic pitfalls in functional neurological disorders - Pimentel, Lucio Huebra, Filho; Mutarelli, Eduardo Genaro (Arquivos de Neuro-Psiquiatria, 2022)
The diagnosis of functional neurological disorders is a major challenge in neurologist practice. Some clinical strategies can facilitate the recognition of functional disorders, but several pitfalls make their diagnosis difficult. Here we highlight the following points of attention during evaluation of patients with functional disorder: not all bizarre behavior is functional; not every event triggered by an emotional factor is a functional disorder; not every topographic incongruity is a functional disorder; patients may present functional and organic symptoms at the same time; psychiatric comorbid condition is not always evident in the history of a functional disorder; problematic communication at the time of diagnosis can compromise treatment and prognosis. In conclusion, we emphasize that special attention to these possible pitfalls facilitate the correct diagnosis and management of functional neurological disorders.
Keywords: Clinical Diagnosis; Somatoform Disorders; Diagnostic Errors